Effect of occupational health nursing practice on musculoskeletal pains among hospital nursing staff in South Korea. Issue 2 (2nd April 2016) - Kim, Yeon-Ha; Jung, Moon-Hee
Abstract : Objective . The purpose of this study was to identify whether occupational health nursing variables serve as the contributing factors to musculoskeletal pains (MSP). Methods . A self-administered questionnaire composed of demographic characteristics, the practice of occupational health nursing and information regarding MSP was designed based on in-depth interviews with eight nurses. This study included 226 hospital nursing staff who worked at three university hospitals located in Seoul, South Korea. Statistical analysis was performed by using SPSS and AMOS 19.0. Results . Shoulder and neck pains occurred when subjects worked more than 46 h/week. Subjects who performed 'work-time adjustment' had lesser chance of having shoulder, leg/foot and wrist/finger pains. Overtime work hours showed an indirect effect on multiple sites of MSP by mediator variable, which was 'work-time adjustment'. Organized night duty days eventually decreased multiple sites of MSP. Conclusion . Administration strategies for nurses to adjust work-time within 46 h/week should be considered.